An unusual cause of dyspareunia: secondary cervical perforation by post placental intrauterine contraceptive device - Chauhan, Monica; Guin, Gita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Postpartum contraception using intrauterine device Copper T 380 A is considered a valuable option to tackle high rate of unintended pregnancy. This case is presented to highlight the importance of follow up and a vigilant examination on patient reporting with any complaint on follow up, even in the presence of a normally placed thread which is crucial to identify problem and manage complication before this reliable, cost effective and long term postpartum contraceptive solution fails to see its rise.